MENYIAPKAN GENERASI BERWAWASAN GLOBAL DENGAN PELATIHAN BAHASA INGRIS KEPADA ANAK USIA SEKOLAH DASAR - Poniman; Muhammad Sirod (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2026)
Abstract This community service program aims to assist the residents of Karangasem Village, Laweyan, Surakarta. Parents in Karangasem who have elementary school-aged children feel the need to enhance their children's English skills. The D3 English Study Program collaborates with Karangasem Village to help them by conducting English training for elementary school-aged children entitled "English Training for Elementary School-Aged Children: Preparing a Globally Minded Generation." This community service program implements the Service Learning method, where the facilitators involve students who actively participate, from preparing the materials to the implementation of the training. The students act as controllers and facilitators of the learning forum, held in 8 sessions. This English training employs specific strategies, namely (1) providing basic and easy materials, (2) using an intensive approach, (3) creating an engaging atmosphere interspersed with games, (4) providing short and humorous stories that contain moral lessons and inspirational social messages. By the end of the activities, they feel eager to learn more about English language skills. Participants recognizing the need for English will continue learning it, understand the importance of English, and possess a global perspective—that is, broadmindedness and the ability to adapt to modern life. Key words: English language, global, ‘service learning', training